PENINGKATAN GAIRAH UMKM PASCA COVID-19 DI DESA ADAT BADUY - Basrowi Basrowi; Furtasan Ali Yusuf; Endang Purwaningsih; Agus Syabarudin (Gapenas Publisher, 2023)
The purpose of this community service is to increase the understanding of the target audience of the Baduy indigenous people in terms of product packaging, product branding, product marketing, and financial management. The method used is by conducting structured training using training methods, question and answer, and direct practice. The number of training participants was 109 people. The implementation time is August 21, 2022 at 10 s.d. 14.00. the place of implementation is at the Kanekes Village Hall Office, Leuidamar District, Lebak Regency. Based on the results of the training, it can be concluded: there was a very significant change in understanding between before and after the training. The trainees became very aware of the importance of packaging, product branding, marketing to tourists, and financial management. The increase occurred by 35% from the average value of 42% to an average of 77%. Through this service activity, follow-up can be carried out, so that the four aspects that are trained can be carried out properly. In other words, the majority of the training participants became more aware of how to improve packaging quality, create product brands, conduct marketing to tourists, and implement financial management